Diffusion Welded Contacts and Related Art Applied to Semiconductor Materials - Korolkov, O.; Sleptsuk, N.; Toompuu, J.; Rang, T. (Elektronika ir Elektrotechnika, 2011)
Today the majority of the contacts for semiconductor devices are prepared by use of standard technologies, when the semiconductor wafer is subordinated to multiple deposition processes and thermal treatments. In this paper we present the basic physical principals and practical realization of diffusion welding technology for fabrication of high quality contacts to semiconductor materials. The paper gives brief details of our previous experience of diffusion welding in semiconductor manufacturing. Here are described the technology and equipment used in the production of power semiconductor devices based on silicon. In parallels to diffusion welded contacts to silicon rectifying elements the same method was successfully developed in application to GaAs structures and SiC large area Schottky diodes. Ill. 8, bibl. 8 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.359